Effectiveness and safety of colistin among older adults: a systematic review and meta-analysis. (5th May 2022) - Margalit, Ili; Prendki, Virginie; Tishler, Ori; Falcone, Marco; Tiseo, Giusy; Leibovici-Weissman, Yaara; Paul, Mical; Yahav, Dafna; ,
Abstract: Objectives: Limited data are available to guide colistin use in older adults (>65 years old). We aimed to assess the effectiveness and safety of colistin in this population. Methods: Systematic review and meta-analysis of original data from randomized control trials, cohort studies and case–control studies assessing colistin regimens with various comparisons for any infection. Original data were obtained from corresponding authors of original studies. The primary outcome was all-cause 1 month mortality; secondary outcomes included clinical and microbiological outcomes and adverse events, including acute kidney injury. Two independent reviewers screened citations, extracted data and assessed risk of bias. ORs with 95% CIs were pooled. Results: We included 38 publications (41 comparisons) reporting 2857 elderly individuals: 29 studies compared a colistin-based regimen versus another regimen (comparison 1) and 10 compared colistin monotherapy versus colistin combination (comparison 2). No significant difference in 1 month mortality was demonstrated between colistin and comparator (comparison 1, OR 1.13, 95% CI 0.80–1.60; comparison 2, OR 0.99, 95% CI 0.78–1.27). Clinical failure was significantly more likely with colistin-based therapy versus comparator (OR 1.52, 95% CI 1.13–2.06). Acute kidney injury was also significantly more common with colistin-based combinations versus other drugs (OR 3.81, 95% CI 2.14–6.77). Conclusions: For older adults, colistin-based therapy resulted in no mortality difference, compared with other regimens, for any infection. Clinical failure and acute kidney injury were significantly more common with colistin-based regimens. Close renal function monitoring is needed while using colistin in older adults.